Shenandoah, 1862 - Time-Life Books (Alexandria, Va. : Time-Life Books, 1997)
This book is by and of the soldiers and civilians who experienced the Shenandoah Valley campaign of 1862. Contains primary source material in the form of personal recollections from letters, diaries, photographs, sketches, and artifacts.
To defend the valley -- Confounding the Yankees -- Stonewall Jackson's way.
Includes bibliographical references (pages 163-164) and index.
Keywords: Shenandoah Valley Campaign, 1862.; Jackson, Stonewall, -- 1824-1863.; Jackson, Stonewall, -- 1824-1863; 1862